2004
DOI: 10.1038/nsmb764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of DrICE inhibition by DIAP1 and removal of inhibition by Reaper, Hid and Grim

Abstract: The Drosophila melanogaster inhibitor of apoptosis protein DIAP1 suppresses apoptosis in part through inhibition of the effector caspase DrICE. The pro-death proteins Reaper, Hid and Grim (RHG) induce apoptosis by antagonizing DIAP1 function. However, the underlying molecular mechanisms remain unknown. Here we demonstrate that DIAP1 directly inhibits the catalytic activity of DrICE through its BIR1 domain and this inhibition is countered effectively by the RHG proteins. Inhibition of DrICE by DIAP1 occurs only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(136 citation statements)
references
References 40 publications
6
127
2
1
Order By: Relevance
“…52 DIAP1 can also bind to processed effector caspases such as DrICE and DCP1 via conserved IAP-binding motifs (IBMs) in the neo-amino-termini of the large caspase subunits. 53 Although some groups report DIAP1 inhibits DrICE, 21 another group suggests that, like cIAP1 and cIAP2, DIAP1 may not inhibit the proteolytic activity of effector caspases even while bound to them. 53 …”
Section: Iapsmentioning
confidence: 99%
“…52 DIAP1 can also bind to processed effector caspases such as DrICE and DCP1 via conserved IAP-binding motifs (IBMs) in the neo-amino-termini of the large caspase subunits. 53 Although some groups report DIAP1 inhibits DrICE, 21 another group suggests that, like cIAP1 and cIAP2, DIAP1 may not inhibit the proteolytic activity of effector caspases even while bound to them. 53 …”
Section: Iapsmentioning
confidence: 99%
“…In apoptotic cells, IAP antagonists such as the Drosophila Reaper, Hid (Head involution defective), and Grim (RHG) proteins (recently reviewed in ref. 3 ) displace IAPs directly from caspases 4,5 which are then released from IAP inhibition, and induce apoptosis. In addition, Reaper, Hid and Grim also promote proteolytic degradation of Drosophila IAP1 (Diap1).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to Ditzel et al, 19 they found that the cleavage of DIAP1 promotes its further degradation via autoubiquitination, that requires the RING-finger domain of the protein. 26 In addition, Yan et al 27 proposed that Dronc cleaves DIAP1 after Glu 205 , resulting in the generation of two separate functional units: (i) a BIR1-containing fragment that inhibits DrICE by binding to it and (ii) a BIR2-RING fragment that can bind Dronc and ubiquitinate it. 27 According to these findings, since the initiator caspase Dronc is probably activated before the effector caspase DrICE, the N-end rule pathway will be involved, if at all, in the removal of the N-terminal BIR1 domain-containing fragment (and even that after further removal of its first 20 N-terminal residues by DrICE), but not in removing the BIR2-RING fragment.…”
mentioning
confidence: 99%
“…26 In addition, Yan et al 27 proposed that Dronc cleaves DIAP1 after Glu 205 , resulting in the generation of two separate functional units: (i) a BIR1-containing fragment that inhibits DrICE by binding to it and (ii) a BIR2-RING fragment that can bind Dronc and ubiquitinate it. 27 According to these findings, since the initiator caspase Dronc is probably activated before the effector caspase DrICE, the N-end rule pathway will be involved, if at all, in the removal of the N-terminal BIR1 domain-containing fragment (and even that after further removal of its first 20 N-terminal residues by DrICE), but not in removing the BIR2-RING fragment. Ryoo et al 9 showed that Rpr-induced removal of DIAP1 occurs in the presence of p35, a strong caspase inhibitor, suggesting that caspase cleavage is not essential for removal of DIAP1 under those conditions.…”
mentioning
confidence: 99%